A Potent Autophagy Inhibitor (Lys05) Enhances the Impact of Ionizing Radiation on Human Lung Cancer Cells H1299 - Cechakova, Lucie; Ondrej, Martin; Pavlik, Vojtech; Jost, Petr; Cizkova, Dana; Bezrouk, Ales; Pejchal, Jaroslav; Amaravadi, Ravi K; Winkler, Jeffrey D; Tichy, Ales (International journal of molecular sciences, 2019)
Autophagy inhibition through small-molecule inhibitors is one of the approaches to increase the efficiency of radiotherapy in oncological patients. A new inhibitor-Lys05-with the potential to accumulate within lysosomes and to block autophagy was discovered a few years ago. Several studies have addressed its chemosensitizing effects but nothing is known about its impact in the context of ionizing radiation (IR). To describe its role in radiosensitization, we employed radioresistant human non-small cell lung carcinoma cells (H1299, p53-negative). Combined treatment of H1299 cells by Lys05 together with IR decreased cell survival in the clonogenic assay and real-time monitoring of cell growth more than either Lys05 or IR alone. Immunodetection of LC3 and p62/SQSTM1 indicated that autophagy was inhibited, which correlated with increased SQSTM1 and decreased BNIP3 gene expression determined by qRT-PCR. Fluorescence microscopy and flow cytometry uncovered an accumulation of lysosomes. Similarly, transmission electron microscopy demonstrated the accumulation of autophagosomes confirming the ability of Lys05 to potentiate autophagy inhibition in H1299 cells. We report here for the first time that Lys05 could be utilized in combination with IR as a promising future strategy in the eradication of lung cancer cells.
Keywords: Apoptosis; Radiation, Ionizing; transmisní elektronová mikroskopie; nádorové buněčné linie; Flow Cytometry; apoptóza; fluorescenční mikroskopie; Lung Neoplasms; lidé; western blotting; Microscopy, Electron, Transmission; průtoková cytometrie; Blotting, Western; Microscopy, Fluorescence; nádory plic; Humans; Cell Line, Tumor; ionizující záření